Association between agronomic traits and aflatoxin accumulation in diverse maize lines grown under two soil nitrogen levels in Eastern Kenya - Mutiga, Samuel K.; Morales, L.; Angwenyi, Samuel; Wainaina, James; Harvey, Jagger J.W.; Das, Biswanath; Nelsona, R.J. (Elsevier, 2017)
Aflatoxin accumulation in maize is strongly influenced by the environment in which the crop is grown. To gain insights into the ways in which soil fertility influences aflatoxin, we investigated the relationships between agronomic traits and aflatoxin in diverse maize testcrosses that were grown under two nitrogen treatment levels. The experiment was conducted in Eastern Kenya, an aflatoxin-endemic area, with natural Aspergillus flavus inoculum. A panel of 205 maize lines was grown under low soil nitrogen (Nlow = 26 kg/ha applied N) in the long season of 2011 and a subset of the genotypes (n = 123) was grown under high soil nitrogen (Nhigh = 114 kg/ha applied N) in the short season of 2010 and long season of 2011. Kernel traits, grain yield, days to anthesis, ear rot, and aflatoxin were analyzed for the panel. Grain yield, protein, and kernel bulk density were higher in maize grown under Nhigh compared to maize grown under Nlow, with grain yield twice as high under Nhigh. A higher proportion of plots had grain with detectable aflatoxin under Nlow than under the Nhigh. When the maize testcrosses were grouped into three maturity categories based on days to anthesis, aflatoxin accumulation was twice as high in the late-maturing group than in the other two categories under Nlow. The proportion of aflatoxin contamination was higher in dent than in flint maize. However, the extent of aflatoxin accumulation did not differ significantly (P > 0.05) over the entire testcross panel, among maize genotypes within the maturity groups or among kernel texture groups within the maturity groups. Kernel bulk density and protein content were higher in early and intermediate groups than in the late maturity group. Grain yield did not differ among the maturity groups (P > 0.05), but significant positive correlations were observed between the proportion of grain yield reduction due to low soil nitrogen stress and aflatoxin in early and late maturity groups. Kernel bulk density was negatively correlated with aflatoxin in grain. No significant association was observed between aflatoxin and ear rot or kernel size. We conclude that aflatoxin mitigation strategies should include soil nitrogen amendment and breeding approaches that include selection for the correlated agronomic traits.